2020
DOI: 10.1002/cre2.376
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the substantivity of silver diamine fluoride in a dentin model

Abstract: Objectives: The goal of endodontic therapy is to prevent apical periodontitis. This is achieved by biomechanical preparation, microbial control using endodontic irrigants, and complete obturation of the canal space. In order to prevent possible postobturation complications and for an added antimicrobial effect, substantivity is a desired characteristic of endodontic irrigants. Currently the most commonly used endodontic irrigant that produces an antibacterial substantivity effect is chlorohexidine (CHX). Silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Propolis is a natural herbal product that has gained increased interest due to its antimicrobial activity against a wide range of pathogenic microorganisms due to the presence of flavonoid content. 15 The antibacterial effect of 2.5% NaOCl was less than that of 3.8% SDF which was consistent with the results of Minavi et al 16 On the other hand, Al-Madi et al 17 found that 3.8% SDF had a significantly larger percentage of dead cells than 2% CHX, but 5.25% NaOCl as a positive control group showed the greatest percentage of dead cells. This may be attributed to the higher concentration of NaOCl that they used.…”
Section: Resultssupporting
confidence: 77%
“…Propolis is a natural herbal product that has gained increased interest due to its antimicrobial activity against a wide range of pathogenic microorganisms due to the presence of flavonoid content. 15 The antibacterial effect of 2.5% NaOCl was less than that of 3.8% SDF which was consistent with the results of Minavi et al 16 On the other hand, Al-Madi et al 17 found that 3.8% SDF had a significantly larger percentage of dead cells than 2% CHX, but 5.25% NaOCl as a positive control group showed the greatest percentage of dead cells. This may be attributed to the higher concentration of NaOCl that they used.…”
Section: Resultssupporting
confidence: 77%
“…Beyond periodontal therapy, SDF has also shown potential benefits for endodontics. 8,9 A concentration of 3.8% SDF used as endodontic irrigant showed substantivity effects in Enterococcus faecalis better than 6.25% sodium hypochlorite. 8 SDF at 3.8% also penetrated dentinal tubules beyond the smear layer, depositing silver salts.…”
Section: Discussionmentioning
confidence: 93%
“…8,9 A concentration of 3.8% SDF used as endodontic irrigant showed substantivity effects in Enterococcus faecalis better than 6.25% sodium hypochlorite. 8 SDF at 3.8% also penetrated dentinal tubules beyond the smear layer, depositing silver salts. 9 Staining in root canals would also not pose an aesthetic concern.…”
Section: Discussionmentioning
confidence: 93%
“…The strain OG1RF is a rifampicin-and fusidic acid-resistant derivative of a caries-related strain OG1 isolated in 1975 [21,22]. Because of its oral rather than urinary origin (e.g., ATCC 29,212), it is commonly used to investigate the pathogenicity of E. faecalis in apical periodontitis [23,24]. We examined the mRNA expression of 84 apoptosisrelated genes, and explored the role of anti-apoptotic and pro-apoptotic members of the BCL-2 family in E. faecalis-induced osteoblast apoptosis.…”
Section: Introductionmentioning
confidence: 99%